Marlborough Recent Acquisitions 1968. (London : Marlborough Fine Art Ltd., 1968)
Andrews, Michael ; Auerbach, Frank ; Bacon, Francis ; Böhler, Hans ; Colville, Alex ; Genoves, Juan ; Grosz, George ; Hepworth, Barbara ; Kitaj, R.B. ; Kokoschka, Oskar ; Kollwitz, Kathe ; Nicholson, Ben ; Nolde, Emil ; Piper, John ; Schiele, Egon ; Smith, David ; Sutherland, Graham
geboortedata per kunstenaar
Engels
Marlborough Recent Acquisitions 1968, Marlborough Fine Art Ltd., London, July - August 1968
boek